Neurological dysfunction screening in a cohort of adolescents with type 1 diabetes: a six-year follow-up - Tinti, Davide; Canavese, Carlotta; Nobili, Cecilia; Marcotulli, Daniele; Daniele, Erika; Rabbone, Ivana; de Sanctis, Luisa (Frontiers in Medicine, 2024)
Diabetic neuropathy (DN) is one of the most insidious microvascular complications in patients with type 1 diabetes (T1DM) and initial signs may appear during childhood. The aim of this study is to evaluate associations between the Nerve Conduction Studies (NCS) outcomes at enrollment with neuropathy screening questionnaires performed six years later in a cohort of asymptomatic adolescents followed up until early adulthood, affected by T1DM.We performed NCS in a cohort of seventy-two adolescents with T1DM and eighteen healthy controls. Six years later, screening questionnaires for DN were proposed: Michigan Neuropathy Screening Instrument (MNSI, specific for symptoms of somatic dysfunction), Composite Autonomic Symptom Score 31 (COMPASS 31, specific for abnormalities of the autonomic component) and Clarke questionnaire (perception of hypoglycemia). Thirty-two TD1M subjects agreed to participate in the follow-up; main clinical-metabolic parameters, including the number of episodes of hypoglycemia in the past twelve months, were collected.11.8% of subjects showed changes compatible with DN through the MNSI questionnaire, while 41% declared a reduced perception of hypoglycemia on the Clarke questionnaire. No significant correlation was observed between the clinical-metabolic parameters or altered response to NCS and scores of MNSI and COMPASS 31 questionnaires. On the other hand, an association was observed between NCS abnormalities and a high number of hypoglycemic events after six years (97-fold increased risk, P=0.009).The frequency of somatic alterations in the study population is 11.8%, whereas the frequency of symptoms correlated with autonomic damage is about 41%. An autonomic impairment recorded at NCS may represent a six-year risk factor for increased hypoglycemic episodes, even if more extensive studies are needed to investigate this possible relationship further.